Sistem Monitoring dan Pengisian Daya Baterai Pada Sepeda Motor Listrik Secara Adaptive - Wilibrodus Wanggur Mboi; Nachrowie Nachrowie; Yandhika Surya Akbar Gumilang; Resi Dwi Jayanti Kartika Sari (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2021)
Development of the automotive world, more and more fuel oil is required to refuel cars. As the price of oil continues to rise, the automotive industry has begun to develop non-petroleum fueled motorcycles, one of which is electric motorcycles. Although it is currently very difficult to completely replace fossil fuels, the introduction of renewable energy sources will be very important to start immediately. One of them is a system to reuse an existing battery charging system on an electric motor in turn, where, when the engine is running, the charging system uses a DC generator located on the electric motor. And when the engine stops, the charging system uses the current source from PLN.